Pengaruh Model Pembelajaran Student Teams Achievement Division (STAD) Berbantuan Chain Squid terhadap Kemampuan Pemahaman Konsep Siswa SD Negeri Ungaran 01 - Aisyah, Assabilla Nasyatul; Putra, Lisa Virdinarti (Universitas PGRI Semarang, 2024)
This research was conducted to the effect of the Student Teams Achievement Division (STAD) learning model assisted by squid chains on the ability to understand concepts. The problem faced is the low ability of students to understand concepts in learning. This type of research is quantitative research. The population used was all students at SD Negeri Ungaran 01, while the research sample was class IA as the experimental class and class IB as the control class. The data collection techniques and instruments used were questionnaires, observation, interviews and documentation. The data analysis technique uses the Independent Sample T-Test and Simple Linear Regression. The results of the research are (1) The different effects of using the Student Teams Achievement Division (STAD) model assisted by Chain Squid on students' conceptual understanding. This is proven by the results of the Independent Sample T-Test with a significance level of less than 0.05, namely 0.006 ˂ 0.05, (2) There is an influence of using the Student Teams Achievement Division (STAD) model assisted by Chain Squid on students' ability to understand concepts. This is proven by the results of the Simple Linear Regression Test with a significance value of less than 0.05, namely 0.018 ˂ 0.05. From the research results, it can be concluded that there is a difference in the ability to understand concepts after using the Student Teams Achievement Division (STAD) model assisted by Chain Squid in 1st grade elementary school student and there is an influence of using the affects the ability to understand concepts in 1st grade elementary school students and the Student Teams Achievement Division (STAD) model assisted by Chain Squid in 1st grade elementary school student.